Melatonin elicits protein kinase C-mediated calcium response in immortalized GT1-7 GnRH neurons - Kelestimur, Haluk; Ozcan, Mete; Kacar, Emine; Alcin, Ergul; Yilmaz, Bayram; Ayar, Ahmet (Elsevier Science Bv, 2012)
Melatonin is suggested to have effects on hypothalamic-pituitary-gonadal (HPG) axis. The pulsatile pattern of GnRH release, which results in the intermittent release of gonadotropic hormones from the pituitary, has a critical importance for reproductive function but the factors responsible from this release pattern are not known. Calcium is a second messenger involved in hormone release. Therefore, investigation of the effects of melatonin on intracellular free calcium levels ([Ca2+](i)) would provide critical information on hormone release in immortalized GnRH neurons. The pattern of melatonin-induced intracellular calcium signaling was investigated by fluorescence calcium imaging using the immortalized GnRH-secreting GT1-7 hypothalamic neurons. Melatonin caused a significant increase in [Ca2+](i), which was greatly blocked by luzindole, a melatonin antagonist, or attenuated by pre-treatment with protein kinase C inhibitor. This study suggests that melatonin seems to have a direct effect on GnRH neurons. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Melatonin; Calcium signaling; GT1-7 cell